Neurohybrid Memristive CMOS-Integrated Systems for Biosensors and Neuroprosthetics - Mikhaylov, Alexey; Pimashkin, Alexey; Pigareva, Yana; Gerasimova, Svetlana; Gryaznov, Evgeny; Shchanikov, Sergey; Zuev, Anton; Talanov, Max; Lavrov, Igor; Demin, Vyacheslav; Erokhin, Victor; Lobov, Sergey; et al. (Frontiers in Neuroscience, 2020)
Here we provide a perspective concept of neurohybrid memristive chip based on the combination of living neural networks cultivated in microfluidic/microelectrode system, metal-oxide memristive devices or arrays integrated with mixed-signal CMOS layer to control the analog memristive circuits, process the decoded information, and arrange a feedback stimulation of biological culture as parts of a bidirectional neurointerface. Our main focus is on the state-of-the-art approaches for cultivation and spatial ordering of the network of dissociated hippocampal neuron cells, fabrication of a large-scale cross-bar array of memristive devices tailored using device engineering, resistive state programming, or non-linear dynamics, as well as hardware implementation of spiking neural networks (SNNs) based on the arrays of memristive devices and integrated CMOS electronics. The concept represents an example of a brain-on-chip system belonging to a more general class of memristive neurohybrid systems for a new-generation robotics, artificial intelligence, and personalized medicine, discussed in the framework of the proposed roadmap for the next decade period.